Design and implementation of remote experimental control platform. (November 2020) - Wang, Chenyang; Lin, Zijian; Li, Ruikai; Chen, Chen
Abstract: Based on the Internet of Things technology, our team has developed a remote wireless control experimental device based on the Internet of Things, which combines traditional experiments with Internet of Things technology. In the example experiment in this paper, the rotation angle of the corresponding motor on the experimental device is changed by means of buttons in the intelligent terminal APP. At the same time, the physical clamping and pushing control function of the control hub is exerted by mechanical push rod, bayonet and other workpieces, an d then the pushing force and rotating force are provided by the motor for the push rod. Finally, the camera is used to monitor the instrument panel and transmit the image data information via the wireless communication module to achieve remote control.